Bioaccumulation and histopathological changes induced by toxicity of mercury (HgCl2) to tilapia fish oreochromis niloticus - Mohammed A. Jasim,; Mohd Sofian-Azirun,; Yusoff, I.,; M. Motior Rahman, (Universiti Kebangsaan Malaysia, 2016)
In this paper we have studied the acute toxicity effect of Hg on hybrid tilapia (Oreochromis niloticus). For this, the tissues of tilapia have been digested by means of acids in microwave oven and was analyzed by flameless atomic absorption spectrophotometer (FAAS). We have identified that the levels of Hg varied significantly in different tissues and the metal concentration was in the following order: liver > gills > muscles; of which the maximum level recorded for Hg was 0.799 mg/kg. We have also observed the alterations towards histopathological aspects in the gills and liver of treated fishes were studied using light and electron microscopy, subjected to the exposure of Hg for 24 h and furthermore we have also noticed the extent of the increased alterations during the 96 h of exposure to median lethal concentration LC50 (0.3 mg/L) a severe disorganization of epithelial cells and modifications of the structure of the secondary lamellae. Moreover the severity has also found to increase to sub-lethal concentration (0.03 mgHg/L) in 21 days of exposure; Liver was slightly affected by the contamination of Hg. Ultimately, histopathology is considered as a sensitive technique of bioaccumulation and for the observing the potential damage from Hg exposure.